The Influence of Consumption of Mackerel Nugget on Changes in Anthropometric Status of Stunting Toddler in Rembang Health Center - Susiyanti, Evi (Universitas Islam Lamongan, 2024)
One of the nutritional problems experienced by Indonesian people is stunting. Stunting is a severe nutritional problem where the impact of stunting can occur in the short term or long term. The consequences of stunting can increase morbidity and mortality during infancy, and lower psychological cognitive function during school years. One real community-based effort that can be made to accelerate overcoming the problem of stunting is by implementing nutritional interventions through a food diversification program from mackerel in the form of nuggets. This research aims to analyze the effect of consuming mackerel nuggets on changes in the anthropometric status of stunted toddlers at the Rembang Community Health Center. This research uses a pre-experimental design with a one-group pre-post-test design. The samples in this study were some stunted toddlers in the work area of the Rembang Health Center, Pasuruan Regency from October 2023 to December 2023 who met the research criteria, consisting of 30 respondents. The sampling technique used is probability sampling with simple random sampling. The data analysis test was carried out using the Wilcoxon sign rank test From the results of the research data analysis, it can be concluded that there is an influence of consumption of mackerel nuggets on changes in the anthropometric status of stunted toddlers with an Asymp Sig (2-tailed) value of 0.000 < significance α (0.05) The use of mackerel fish processed in the form of nuggets can be used as an alternative in providing complementary food to stunted toddlers. Food diversification is the key to success in increasing the appetite of stunted toddlers, whereby by increasing the appetite experienced by toddlers, the problem of stunting will be easier to solve. Keywords: Nugget, Mackerel Fish, Toddlers, Stunting, Anthropometrics